Analisis Biaya dan Luaran Klinis Sindrom Koroner Akut Berbasis Clinical Pathway - Susan Fitria Candradewi; Dyah Aryani Perwitasari; Nabilah Nabilah (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2021)
Health clinicians often show different variations in the choice of therapy they prescribe for patients depending on their expertise, knowledge, and even their art. This is likely to affect several things, including the cost that patients have to pay. Such a difference in costs is avoidable by applying scientific evidence-based medical service standards and having measurable outcomes known as Clinical Pathways. A clinical pathway serves as a tool to measure the quality of health services based on the standardization of the treatment process. This research was designed to determine the cost analysis of treatments received by patients with acute coronary syndrome (ACS) according to the clinical pathway. This non-experimental research employed a retrospective cohort study design. The data were gathered from the medical records of ACS patients who were treated at the ICCU of PKU Muhammadiyah Hospital in Yogyakarta, and the costs incurred were compared between treatments that matched and did not match the clinical pathways. The inclusion criteria were ACS patients treated during 2016 who were between ≥ 18 and <75 years old and had complete data. Meanwhile, the exclusion criteria were ACS patients who had incomplete data, tumor malignancy, and a creatinine level of > 3 mg/dL. Here, therapies given to patients are concluded to fit the clinical pathway if they are precisely the same (100%) as the Clinical Practice Guide used by this hospital. The clinical outcome was measured from the patient’s length of stay (LOS). During the data analysis, the costs of ACS patient treatments that were compliant and non-compliant with the clinical pathway were compared based on the level of severity using the Mann-Whitney test in the SPSS program. The results showed that of the 63 patients, 31 received treatments according to the clinical pathway, while the other 32 did not. The average LOS of the former and the latter were, respectively, 4.45 and 5.53 (p= 0.043), with the total costs of treatments up to IDR5,474,001,73 and IDR6,728,153.13 (p= 0,154). Conformity to a clinical pathway significantly influences the length of stay but does not affect the cost of care for acute coronary syndrome patients.